Combined TRAF6 Targeting and Proteasome Blockade Has Anti-myeloma and Anti-Bone Resorptive Effects - Chen, Haiming; Li, Mingjie; Sanchez, Eric; Wang, Cathy S.; Lee, Tiffany; Soof, Camilia M.; Casas, Christian E.; Cao, Jasmin; Xie, Colin; Udd, Kyle A.; DeCorso, Kevin; Tang, George Y.; et al. (Molecular cancer research, 2017)
TNF receptor–associated factor 6 (TRAF6) has been implicated in polyubiquitin-mediated IL1R/TLR signaling through activation of IκB kinase (IKK) to regulate the NF-κB and JNK signaling pathways. Here, TRAF6 protein was determined to be overexpressed in bone marrow mononuclear cells (BMMC) from patients with multiple myeloma. TRAF6 expression in BMMCs from patients with progressive disease is significantly elevated as compared with individuals in complete remission, with monoclonal gammopathy of undetermined significance, or healthy subjects. Furthermore, TRAF6 dominant–negative (TRAF6dn) peptides were constructed which specifically reduced TRAF6 signaling and activation of IKK. TRAF6 not only reduced cellular growth but also increased the apoptosis of multiple myeloma tumor cells in a concentration-dependent fashion. Because TRAF6 activates IKK through polyubiquitination, independent of its proteasome activity, a TRAF6dn peptide was combined with the proteasome inhibitors bortezomib or carfilzomib to treat multiple myeloma. Importantly, targeting of TRAF6 in the presence of proteasome inhibition enhanced anti–multiple myeloma effects and also decreased TLR/TRAF6/NF-κB–related signaling. Finally, TRAF6dn dose dependently inhibited osteoclast cell formation from CD14+ monocytes, induced with RANKL and mCSF, and markedly reduced bone resorption in dentin pits. In all, these data demonstrate that blocking TRAF6 signaling has anti–multiple myeloma effects and reduces bone loss. Implications: The ability to target TRAF6 signaling and associated pathways in multiple myeloma suggests a promising new therapeutic approach. Mol Cancer Res; 15(5); 598–609. ©2017 AACR.